Carbon, nitrogen and phosphorus allocation in agro-ecosystems of a West African savanna I. The plant component under semi-permanent cultivation - (:unkn) unknown (My University, 2002)
Organic matter (OM) is both a commodity and a means of production in low-input farming systems of sub-Saharan Africa. Since this resource is becoming increasingly scarce in West African savannas (WAS), there is a need to assess OM, carbon (C), nitrogen (N), and phosphorus (P) allocation in local ecosystems related to land management. Carbon, N and P storage under semi-permanent cultivation in savannas in southern Senegal was thus measured through a chronosequence including 25 groundnut (Arachis hypogaea L.) crops and plots left to fallow for 1-26 years. The amounts of C, N and P in cropped C they increased to 17.7 t C, 231 kg N and 19.6 kg P ha(-1) in fallow plots aged plots were 5.5 t C, 106 kg N and 5.9 kg P ha(-1), 1-9 years. A threshold was reached after 10 years of fallow. Beyond it biomass amounts remained steady. Older fallow plots stored 29 t C, 333 kg N and 33.8 ka P ha(-1). Highest increases in woody components were found within the very first year following crop abandonment, and were achieved at the expense of the herbaceous layer. Carbon and nutrient allocation to woody below-ground biomass occurred only later. Massive nutrient losses were expected to occur at clearing due to both burning and wood exportation. Because storage in woody and herbaceous biomass remained steady in fallows aged more then 10 years, young fallows were found to have the highest productivity for wood and forage. However, plant productivity relied on the high resprouting capacity of local tree species, and thus on the maintenance of long breaks of fallow needed for the maintenance of perennial rooting systems. One of the aims of programs to improve the management of fallows, or to replace them with agroforestry techniques, should thus be to preserve perennial rooting systems by any means that are possible in the cropping systems of the WAS. (C) 2002 Elsevier Science B.V All rights reserved.
Keywords: African Research